2014
DOI: 10.15314/tjse.201439611
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 8 week step-aerobic exercises on (state and trait) anxiety levels and quality of life of women

Abstract: The aim of this paper is to compare and determine anxiety levels and quality of life of women doing regular 8-week stepaerobic exercise and who didn't and to examine the effects of exercises on these parameters. Ninety six voluntary people, 48 in experimental group and 48 in control group, took part in the study. Average age, height, weight of the women comprising experimental and control groups, are 27.23 ± 9.02 years, 164.4627.23 ± 5.31 cm, 70.63±12.35 kg and 32.94 ±9.12 years, 164.56 ±6.36 cm, 65.33 ± 9.55,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Therefore, it may be stated that health plays an important role for students to maintain their life. Sevinç et al (2014) in their study entitled "The Effects of 8-week Step-Aerobics Exercise (situational and Continuous) on Women"s Levels of Anxiety and on their Life Quality", investigated the life quality levels of women who had done step-aerobics exercise regularly for 8 weeks and the life quality levels of women who did not do any sports, and thus they found that sport had positive effects on women"s life quality.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it may be stated that health plays an important role for students to maintain their life. Sevinç et al (2014) in their study entitled "The Effects of 8-week Step-Aerobics Exercise (situational and Continuous) on Women"s Levels of Anxiety and on their Life Quality", investigated the life quality levels of women who had done step-aerobics exercise regularly for 8 weeks and the life quality levels of women who did not do any sports, and thus they found that sport had positive effects on women"s life quality.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is known that individuals engaged in sports activities are both physically and mentally healthier [13]. In addition, it is stated that regular physical activity causes positive effects on the psychology of individuals and is an important factor in preventing negative emotional states such as anxiety [14,15]. The precautions are taken due to the virus cause individuals' eating habits to change and weight gain [16].…”
Section: Introductionmentioning
confidence: 99%